A distributed routing protocol for predictable rates in wireless mesh networks - Arzani, Behnaz; Guerin, Roch; Rebiero, Alejandro (Network Protocols (ICNP), 2012 20th IEEE International Conference on, 2012)
A distributed routing protocol for predictable rates in wireless mesh networks Behnaz Arzani, Roch Guerin, Alejandro Ribeiro Wireless mesh networks hold the promise of rapid and flexible deployments of communication facilities. This potential notwithstanding, the often erratic behavior of multihop wireless transmissions is limiting the range of applications that such networks can target. In this paper we investigate the feasibility and benefits of a routing protocol explicitly aimed at making wireless mesh networks more predictable while preserving their efficiency and flexibility. The protocol's basic premise is the classical idea that a multipath solution can offer resiliency to unexpected link variations. The paper's contributions are in demonstrating how this can be effectively realized in a wireless context, and in offering initial evidences of its efficacy. In particular, the paper illustrates how routing decisions that account for link variability can be computed in a distributed fashion, and the benefits they afford in improving the stability of end-to-end transmission rates even in the presence of random network fluctuations